Teknologi Menurut Perspektif Barat dan Islam - Wan Mohamed Radzi, Che Wan Jasimah; Bakar, Osman (Jurnal Usuluddin, 1996)
Science is always associated with technology and the success of technology depends on how human intelligence manipulates science. In the modern world, the use of technology does not consider moral values. As a result technology has helped to bring about destruction and decadence to human society and the environment. It is time to review the definition of technology so that religious and social values are taken into account for the betterment of the human race.